Formação de Portfólio: uma alternativa não paramétrica para o mercado de ações - Vasconcelos, Ricardo Nelson (2004)
The purpose of this paper is testing an alternative method to create an efficient portfolio, from the technical efficiency ranking of the bonds negociated in BOVESPA from october/1998 to september/2003, using the non parametric model of data envelopment analysis.To the creating of efficient portfolios, is using the Markowitz portfolio theory, comparing to the selecting assets to the composition of best portfolios DEA model from Elton Grubber. To establish the index of efficiency was calculated the average prices quotation of bonds negociated in Bovespa. Comparing the methods, it was verified the best performance of portfolios using the DEA methodology in relation to the traditional Elton Gruber model to get a best level of return compared to the risk of portfolios.